‘Can We See It?’: Contextualizing ‘Deforestation’ from an English-Medium Science Textbook for a Primary School Level - Ahmad Sugianto (J-Lalite: Journal of English Studies, 2021)
Understanding an English-medium science textbook is possibly challenging for some students. It is, for example, due to the language used. To deal with this issue, construing the use of the other mode, such as visual images, along with the verbal text is regarded useful. Thereby, the construal of multimodality in an English-medium science textbook becomes crucial. Albeit a myriad of inspections on multimodality exists, but to the best of the writer’s knowledge, such investigation with respect to an English-medium science textbook, particularly at a primary school level, was found to be limited. Therefore, this study aimed to scrutinize the verbal text and visual image presented in a science textbook used for a primary school level which is presented in English. To that end, a descriptive research design was employed. In this regard, a systemic functional multimodal discourse analysis (SF-MDA) within the trinocular metafunctions encompassing ideational, interpersonal, and textual metafunctions was utilized. The systemic functional linguistics theory, the grammar of visual design, intersemiotic complementarity, and logico-semantics were the frameworks employed to analyze the artefact, the English-medium science textbook. The findings revealed that the visual image and verbal text interact with one another within the three metafunctions. Given the interaction between the two modes, the present study suggests that both teachers and students are required to take into considerations and be aware of the potential or roles of images along with the verbal text, i.e. the images are not merely accessories, but instead, these are able to assist the comprehension of the science materials learned.